Pointing in Intelligent Environments with the WorldCursor - Wilson, Andy; Pham, Hubert (Proceedings of IFIP INTERACT03: Human-Computer Interaction 2003, 2003)
We introduce the WorldCursor, a pointing device and cursor designed for intelligent environments. The WorldCursor is analogous to the mouse and cursor used in traditional GUIs: the user may select and interact with a physical device by positioning the cursor on the device and clicking. We use the XWand (Wilson, 2003) as a physical pointing mechanism, and couple it with the WorldCursor device which projects a cursor on the physical environment. The WorldCursor improves upon the XWand by removing the need for external positioning technology such as video cameras. We detail the device and signal processing algorithms, and discuss its application in intelligent environments.